Who am I? Sense of identity of Portuguese university students in a socio-ecological perspective - Żyłkiewicz-Płońska, Emilia; Coimbra, Susana (Kultura-Społeczeństwo-Edukacja, 2024)
The transition to adulthood, in Portugal as in most countries, has undergone profound changes in the last decades. They are mostly related to the extension of educational paths and the later and less linear entry into the labor market. Emerging adulthood (EA) resulted from a context of long school journeys, uncertain and precarious transitions to the labor market, and postponed life projects such as autonomy regarding family of origin, marriage or parenthood. One of the key features of this developmental phase is identity exploration. It involves experiencing a dynamic process of exploration and reflection in both: individual aspects and socio-ecological contexts. This study explores the self-identification of Portuguese students, based on the assumptions of Bronfenbrenner’s ecological model. The aim of the study was to analyse the development of an individual’s sense of identity resulting from participation in the surrounding socio-cultural conditions. The surveyed psychology students (N = 107) aged between 20–25 (M = 21.4;SD = 1.44), mostly female (94.4%) provided answers to the question Who am I? using the TST (Twenty Statement Test) by Kuhn and McPartland. The collected material was analysed using qualitative content analysis with categories defined according to Bronfenbrenner’s model. Results suggest that surveyed EAs defined themselves mostly according to individual features, in particular personality, character and emotional states. Surprisingly, frequently, participants identified themselves as someone who is involved in social relations above the microsystems and with nature (mesosystem categories). Identifications of microsystem sources also seem to play an important role in the way participants described themselves, in particular as a friend and/or peer, as a family member, as a student, and as an aspiring professional. The least valued ecological systems were the exosystem (e.g. membership of an organisation) and macrosystem (e.g. nationality).